2021
DOI: 10.31557/apjcp.2021.22.5.1561
|View full text |Cite
|
Sign up to set email alerts
|

The Platelet to Lymphocyte and Neutrophil to Lymphocyte Ratios in Predicting Response to Platinum-based Chemotherapy for Epithelial Ovarian Cancer

Abstract: Objective: The patients with advanced-stage ovarian cancer have higher factors complicating surgery; thus, the best choice for them is surgery with chemotherapy with six cycles of adjuvant chemotherapy. Generally, chemotherapy can be evaluated in various ways, phsychal examination, radiology examination, and laboratory examination. This study aims is to examine if the measurement of the platelet/lymphocyte ratio (PLR) and neutrophil/lymphocyte ratio (NLR) can be used to predict a patient's response to chemothe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…75 Numerous subsequent studies confirmed that an elevated NLR prior to surgery or treatment correlated with unfavorable surgical results, drug resistance, and decreased efficacies of immunotherapy and chemotherapy. [76][77][78][79] Elevated NLRs have been seen in both meningioma and gliomas, with a lack of significance attributed to extracranial influences of alternative inflammation sources. 43 The specific difference in NLR values for meningioma versus those of other brain pathologies has not been fully identified, so further research in meningioma is warranted moving forward.…”
Section: Discussionmentioning
confidence: 99%
“…75 Numerous subsequent studies confirmed that an elevated NLR prior to surgery or treatment correlated with unfavorable surgical results, drug resistance, and decreased efficacies of immunotherapy and chemotherapy. [76][77][78][79] Elevated NLRs have been seen in both meningioma and gliomas, with a lack of significance attributed to extracranial influences of alternative inflammation sources. 43 The specific difference in NLR values for meningioma versus those of other brain pathologies has not been fully identified, so further research in meningioma is warranted moving forward.…”
Section: Discussionmentioning
confidence: 99%
“…In patients who underwent debulking surgery, a high PLR had a negative correlation with DFS and OS [286]. Winarno et al discovered that a high post-operative PLR ratio of patients with an EOC was associated with an increase in the response to platinum-based chemotherapy [287]. Several researchers have also shown that PLR could play a predictive role in the early diagnosis and in distinguishing between benign and malignant tumors [269,270,288,289].…”
Section: Plateletsmentioning
confidence: 99%